Penerapan Metode Certainty Factor Dalam Perancangan Aplikasi Diangnosa Penyakit Kulit Dengan Jenis Kosmetik - Subianto, Roby; Juledi, Angga Putra; Masrizal, Masrizal (MEANS (Media Informasi Analisa dan Sistem), 2023)
Skin is the outermost organ of the body that covers the human body. The skin makes up 15% of the total body weight. On the outer surface of the skin there are pores (cavities) where sweat is released. The skin has many functions, including as body armor, as a sense of touch or communication tool, and as a temperature regulator. Most people, especially women, have white, healthy, clean and well- groomed facial skin. Cosmetics Distributor is a line of business that sells cosmetic products. In identifying the consumer's facial skin type, it is carried out by employees who are not experts. Often there is an error asking the type of skin and to hire a doctor or expert requires a large amount of money. The problems in using products that do not pay attention to skin type or do not know it, causing new problems such as acne, dry skin and others. These problems can be solved by the field of science in detecting a person's facial skin based on expert knowledge, then the science is an Expert System using Certainty factor. The results of this study can identify the type of facial skin based on the existing symptoms, it is hoped that it can help distributors and detect skin quickly and accurately.